2015
DOI: 10.5772/60910
|View full text |Cite
|
Sign up to set email alerts
|

Facile Preparation of Silver Halide Nanoparticles as Visible Light Photocatalysts

Abstract: In this study, highly efficient silver halide (AgX)-based photocatalysts were successfully fabricated using a facile and template-free direct-precipitation method. AgX nanoparticles, which included silver chloride (AgCl), silver bromide (AgBr) and silver iodide (AgI), were synthesized using different potassium halides and silver acetate as reactive sources. The size distribution of the AgX nanoparticles was determined by the reaction time and ratio of the reagents, which were monitored by UV-vis spectra. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
2
10
0
1
Order By: Relevance
“…This evidence confirms the theoretic stoichiometric atomic ratio between Ag and Cl atoms in AgCl. The data were in agreement with those documented elsewhere [ 30 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…This evidence confirms the theoretic stoichiometric atomic ratio between Ag and Cl atoms in AgCl. The data were in agreement with those documented elsewhere [ 30 ].…”
Section: Resultssupporting
confidence: 92%
“…The x - and y -axis labels were energy/keV and count/cps, respectively [30]. The EDX spectra of AgCl-NPs–loaded exopolysaccharide nanocomposite confirm the existence of silver and chlorine atoms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…22 Cui et al reported on the facile preparation of silver halide nanoparticles on visible light photocatalysts. 23 Interestingly, as the size of Ag NPs changes during the reaction, their unique properties dissipate and change as well. 24 Accordingly, mutual contact between the Ag NPs and their aggregation renders them unstable.…”
Section: Introductionmentioning
confidence: 99%